Use of a heart rate meter in swimming and athletic performance measurement - Treffene, R. J.; Alloway, J.; Jull, J. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
Swimming efficiency has been investigated by many researchers, including Holmer (1974) and di Prampero et al. (1974). di Prampero and his associates deduced a relationship between swimming efficiency (E), bodydrag (Db), swimming speed (V), and net oxygen uptake (Vo2). Using two submaximal speeds (0.55 and 0.90 m/sec) di Prampero et al. (1974) showed that E/Db remained relatively constant in this range. Treffene (1975) investigated the relationship between the velocity of swimming and heart rate (HR) for swimmers and suggested that a linear relationship existed and yielded a constant value for E/Db. The use of heart rates to evaluate swimming performance requires a technique to measure heart rate. The technique described here requires a test in a swimming pool that is similar to a bicycle ergometer test. If a subject swims for more than 2 min at a constant pace, his heart rate will become steady after about 40 sec. This steady rate is characteristic of the use of oxygen at that speed. Therefore, if the heart rate is measured either during the swim or "immediately" after the swim, that rate is an indirect measure of the oxygen consumption at that speed. It is important to determine the heart rate immediately after the swim or within 5 sec of cessation of the exercise because the heart rates of elite swimmers decrease very rapidly. This study was directed at using a heart rate meter constructed for pool heart rate measurement to determine the velocity-heart rate curves for swimmers .